2011
DOI: 10.1007/s00266-011-9829-2
|View full text |Cite
|
Sign up to set email alerts
|

Using Multidetector Row Computed Tomography to Evaluate Baggy Eyelid

Abstract: BackgroundBaggy eyelids, formed by intraorbital fat herniation in the lower eyelids, are a sign of aging observed in the midface. This study aimed to identify the cause of baggy eyelids by evaluating the relationship between orbicularis oculi muscle thickness, orbital fat prolapse length, and age using multidetector row computed tomography (MDCT).MethodsThe 34 patients in the study ranged in age from 20 to 79 years. The patients were divided into three age groups: 20–29 years, 30–54 years, and 55–79 years. Orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Decreased orbicularis muscle thickness has been correlated to increased lower lid fat prolapse and the formation of steatoblepharon. 13 Measuring a lower lid is simple and can be performed with a small, flexible ruler found in most clinics. This should become a standard recorded measurement for patients seeking blepharoplasty, along with the standard upper lid crease, fissure width, and levator function.…”
Section: Plastic and Reconstructive Surgery • August 2015mentioning
confidence: 99%
“…Decreased orbicularis muscle thickness has been correlated to increased lower lid fat prolapse and the formation of steatoblepharon. 13 Measuring a lower lid is simple and can be performed with a small, flexible ruler found in most clinics. This should become a standard recorded measurement for patients seeking blepharoplasty, along with the standard upper lid crease, fissure width, and levator function.…”
Section: Plastic and Reconstructive Surgery • August 2015mentioning
confidence: 99%
“…In addition, we determined that SMAS laxity was greater in older subjects and that changes in their facial appearance were easily induced by a PC (Figure ). Our previous studies, in which the SMAS laxity was quantified using MDCT, revealed the usefulness of the imaging modality . Nonetheless, our current results provide objective evidence of the relationship between age and SMAS laxity, which is a significant cause of cheek sagging.…”
Section: Discussionmentioning
confidence: 53%
“…To this end, the MDCT imaging modality was used to accurately measure the morphological changes in the SMAS that were associated with a posture change. Current CT imaging technology can provide high‐resolution images, allowing detailed visualization of the facial appearance and the subcutaneous anatomic structures . Moreover, the workstation, which serves as the image analysis device, can create various 3‐D CT images as well as reconstructed images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, multi-detector-row CT (MDCT) can provide three-dimensional (3D) CT images (8) of face and body shape, as well as subcutaneous structures (4,5,9,10).…”
mentioning
confidence: 99%